PENGARUH TERAPI MUROTTAL AL QUR’AN TERHADAP INTENSITAS NYERI PADA PASIEN GAGAL GINJAL KRONIK (GGK) YANG MENJALANI HEMODIALISIS DI RSU SEMBIRING DELI TUA - Rini Debora Silalahi (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2026)
Chronic kidney failure (CKF) is a condition that causes a gradual and irreversible decline in kidney function, requiring hemodialysis therapy in the end-stage of the disease. One of the problems patients often experience during hemodialysis is pain. The. Quran recitation therapy, which is safe and easy to use, is a non-pharmacological approach to pain management. The purpose of this study was to determine how Al-Qur'an murottal therapy affects the pain intensity of patients suffering from chronic kidney failure and undergoing hemodialysis at Sembiring Deli Tua General Hospital. This study used a quantitative design with a quasi-experimental approach. It used a single group pretest-posttest design. The sampling method was used to select the research sample from 21 respondents. Before and after Al-Qur'an murottal therapy for ±15 minutes, pain intensity was measured using the Numeric Rating Scale (NRS). The Wilcoxon Signed Rank test was used to analyze univariate and bivariate data. The results showed that Al-Qur'an murottal therapy reduced pain intensity. There was a significant relationship between Al-Qur'an murottal therapy and decreased pain intensity in chronic kidney failure patients undergoing hemodialysis, according to the results of statistical tests, with a p value of 0.001 (p <0.05). This study found that Al-Qur'an murottal therapy significantly reduced the pain intensity of CKD patients undergoing hemodialysis. Therefore, this therapy can be recommended as a non-pharmacological intervention to help reduce pain and improve patient comfort during hemodialysis.